Begonia yentuensis and B. khaucaensis (Begoniaceae), two new species from northern Vietnam - Luu, Hong Truong; Duong, Quoc Hung; Le, Khac Quyet; Lin, Che-Wei (Phytotaxa, 2022)
Two new species of Begonia from northern Vietnam, B. yentuensis and B. khaucaensis, are described. The first new species, B. yentuensis, is similar to B. asperifolia Irmsch., the two species share several characters such as tuberous habit, subsymmetric foliage, 4-tepaled staminate flowers and pistillate flowers with 5 tepals, but B. yentuensis is different in its shorter petioles up to 7 (vs. to 20) cm long and leaves nearly appressed to the substrate (vs. not appressed to substrate), filaments fused at base (vs. fused at base into a column ca. 2 mm long), anthers apex rounded (vs. acute to mucronate) and placentae unilamellate (vs. bilamellate). Moreover, B. asperifolia is found only at high elevations (1,500–3,400 m), while B. yentuensis was collected at a low elevation (ca. 500 m). The other new species, B. khaucaensis resembles B. jubar V.T.Pham & C.W.Lin in its rhizomatous habit, number of tepals of both staminate and pistillate flowers, ovary 3-loculed and placenta bilamellate, but differs from the latter for having hairy (vs. glabrous) stipules and petiole, suborbicular to reniform leaves (vs. ovate to widely ovate leaves, slightly polygonal in outline), bracts margin entire (vs. denticulate to serrate with very short soft hairs) and ovary wings crescent-shaped (vs. triangular).